MAGE-Targeted Gold Nanoparticles for Ultrasound Imaging-Guided Phototherapy in Melanoma - Li, Xuelin (Biomed Res Int, 2020)
Gold nanorods exhibit a wide variety of applications such as tumor molecular imaging and photothermal therapy (PTT) due to their tunable optical properties. Several studies have demonstrated that the combination of other therapeutic strategies may improve PTT efficiency. A method called optical droplet vaporization (ODV) was considered as another noninvasive imaging and therapy strategy. Via the ODV method, superheated perfluorocarbon droplets can be vaporized to a gas phase for enhancing ultrasound imaging; meanwhile, this violent process can cause damage to cells and tissue. In addition, active targeting through the functionalization with targeting ligands can effectively increase nanoprobe accumulation in the tumor area, improving the sensitivity and specificity of imaging and therapy. Our study prepared a nanoparticle loaded with gold nanorods and perfluorinated hexane and conjugated to a monoclonal antibody (MAGE-1 antibody) to melanoma-associated antigens (MAGE) targeting melanoma, investigated the synergistic effect of PTT/ODV therapy, and monitored the therapeutic effect using ultrasound. The prepared MAGE-Au-PFH-NPs achieved complete eradication of tumors. Meanwhile, the MAGE-Au-PFH-NPs also possess significant ultrasound imaging signal enhancement, which shows the potential for imaging-guided tumor therapy in the future.